INDUSTRY IS THE MAIN CRITERIA OF THE ECONOMY (International Conference on Medical Science, Medicine and Public Health, 2025)
Industry plays a leading role in the world economy. Industry determines the economic potential of countries, the technical level of production, the level of use of natural, material and labor resources. All the main directions of development of productive forces and territorial organization, the solution of the most important economic and social problems of developed and developing countries are associated with industry.